1992
DOI: 10.1113/jphysiol.1992.sp019429
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of quantal content to decreased postsynaptic sensitivity at single endplates in alpha‐bungarotoxin‐treated rats.

Abstract: SUMMARY1. Rats were injected once every 48 h with a-bungarotoxin (aBTX) for periods up to 6 weeks. Injections caused weakness of facial muscles which lasted about 8 h. Hemidiaphragms were dissected for biochemical and electrophysiological measurements.2. In muscles from animals treated for 2-3 weeks with toxin, the binding of 125-aBTX was reduced to 58 %, and the ACh content to 81 % of control values. Choline acetyltransferase activity was unchanged. ACh release evoked by 3 Hz nerve stimulation was increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
149
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 26 publications
18
149
1
Order By: Relevance
“…The increase of motoneuron excitability observed in this study (Fig. 2) and the increase of ACh release observed by others after AChR blockade (Plomp et al, 1992(Plomp et al, , 1994) may both be initiated by lost retrograde signaling and represent an integrated attempt by the motoneuron to maintain motor unit force output in the face of decreased AChR density at the endplate. Although retrograde signaling from muscle may be vital for determining motoneuron functional properties, it is also important to keep in mind the pivotal role of anterograde signaling from motoneurons for establishing mechanisms that likely enable retrograde signaling via AChR activation.…”
Section: Roles Of Retrograde Signalingsupporting
confidence: 69%
See 1 more Smart Citation
“…The increase of motoneuron excitability observed in this study (Fig. 2) and the increase of ACh release observed by others after AChR blockade (Plomp et al, 1992(Plomp et al, , 1994) may both be initiated by lost retrograde signaling and represent an integrated attempt by the motoneuron to maintain motor unit force output in the face of decreased AChR density at the endplate. Although retrograde signaling from muscle may be vital for determining motoneuron functional properties, it is also important to keep in mind the pivotal role of anterograde signaling from motoneurons for establishing mechanisms that likely enable retrograde signaling via AChR activation.…”
Section: Roles Of Retrograde Signalingsupporting
confidence: 69%
“…In eight fibers, the amplitude of the fourth EPC in a 50 Hz train was 37.6 Ϯ 4.4% (n ϭ 8) of the first EPC amplitude, whereas the same comparison yielded 80.3 Ϯ 1.5% in four control experiments, each of which included sampling from at least seven fibers. Previous studies have shown that the amount of ACh released at motor terminals increases significantly after several weeks of partial AChR blockade with ␣-btx, and this is thought to be a compensatory response to decreased AChR density (Plomp et al, 1992(Plomp et al, , 1994. The increased EPC amplitude depression during low-and high-frequency activation might thus reflect an increased quantal content at motor terminals.…”
Section: Bungarotoxinmentioning
confidence: 96%
“…This led us to speculate that retrograde signaling from the muscle to motoneuron is altered in the Dys mutant. Retrograde signaling pathways influencing neurotransmitter release have also been inferred in previous murine and Drosophila studies (Plomp et al, 1992;Davis and Bezprozvanny, 2001;Turrigiano and Nelson, 2004), including those focused on the Drosophila larval NMJ (Marqués and Zhang, 2006). Little is known, however, about the components of these pathways.…”
Section: Introductionmentioning
confidence: 92%
“…To minimize errors in the quantal content estimation, we have corrected the effect of nonlinear summation on EPP amplitude as previously described (McLachlan and Martin, 1981) using a correction factor ( f ϭ 0.8) (see Materials and Methods). The introduction of that factor improves overcorrection introduced by older methods (Martin, 1955), and it has been used in different mouse neuromuscular preparations (Plomp et al, 1992;Wood and Slater, 1997;Bullens et al, 2002;Bewick et al, 2004;Chen et al, 2010). Current-clamp measurements of quantal content could be relatively inaccurate if compared with absolute quantal content values obtained with voltage-clamp recordings as previously described in other preparations (Wood and Slater, 1997).…”
Section: Increased Quantal Content and Strong Synaptic Depressionmentioning
confidence: 99%